Optimizing Milling Margins: Implementing Sell-or-Continue Decisions in Paddy Production in Moncongloe Lappara Village, Indonesia - Muh Rum; Hafidzh Fachmy Rum (Golden Ratio of Mapping Idea and Literature Format, 2026)
This study aims to optimize profit margins for farming businesses in Moncongloe Lappara Village through a "Sell or Process Further" tactical decision analysis. Farmers often sell raw grain for liquidity, disregarding potential lost added value. Using a quantitative descriptive approach and Differential Cost Analysis, this research compares the profitability of selling Dry Harvested Grain (GKG) versus processing it into rice. Field data simulations based on a 1-ton input indicate that further processing yields an additional net benefit of IDR 942,000 per ton, equivalent to a 12.5% margin increase compared to direct selling. Another significant finding is that by-product sales (bran) cover 82% of incremental processing costs, thereby minimizing operational risk. Consequently, the further processing strategy is shown to be feasible and recommended to enhance the economic welfare of local business owners.